Functional relations between locomotor performance traits in spiders and implications for evolutionary hypotheses - Prenter, John (BioMed Central, 2010)
BACKGROUND: Locomotor performance in ecologically relevant activities is often linked to individual fitness. Recent controversy over evolution of extreme sexual size dimorphism (SSD) in spiders centres on the relationship between size and locomotor capacity in males. Advantages for large males running over horizontal surfaces and small males climbing vertically have been proposed. Models have implicitly treated running and climbing as functionally distinct activities and failed to consider the possibility that they reflect common underlying capacities. FINDINGS: We examine the relationship between maximum climbing and running performance in males of three spider species. Maximum running and climbing speeds were positively related in two orb-web spiders with high SSD (Argiope keyserlingi and Nephila plumipes), indicating that for these species assays of running and climbing largely reveal the same underlying capacities. Running and climbing speeds were not related in a jumping spider with low SSD (Jacksonoides queenslandica). We found no evidence of a performance trade-off between these activities. CONCLUSIONS: In the web-spiders A. keyserlingi and N. plumipes good runners were also good climbers. This indicates that climbing and running largely represent a single locomotor performance characteristic in these spiders, but this was not the case for the jumping spider J. queenslandica. There was no evidence of a trade-off between maximum running and climbing speeds in these spiders. We highlight the need to establish the relationship between apparently disparate locomotor activities when testing alternative hypotheses that yield predictions about different locomotor activities. Analysis of slopes suggests greater potential for an evolutionary response on performance in the horizontal compared to vertical context in these spiders.